Symptomatic Abdominal Simple Cysts: Is Percutaneous Sclerotherapy with Hypertonic Saline and Bleomycin a Treatment Option? - V. D. Souftas; M. Kosmidou; M. Karanikas; D. Souftas; G. Menexes; P. Prassopoulos (Gastroenterology Research and Practice)
Aim. To evaluate the feasibility of percutaneous sclerotherapy of symptomatic simple abdominal cysts, using hypertonic saline and bleomycin, as an alternative to surgery. Materials and Methods. This study involved fourteen consecutive patients (ten women, four men, mean age: 59.2 y) with nineteen symptomatic simple cysts (liver n=14, kidney n=3, and adrenal n=2) treated percutaneously using a modified method. Initially CT-guided drainage was performed; the next day the integrity of the cyst/exclusion of extravasation or communications was evaluated under fluoroscopy, followed by two injections/reabsorptions of the same quantity of hypertonic NaCl 15% solution and three-time repetition of the same procedure with the addition of bleomycin. The catheter was then removed; the patients were hospitalized for 12 hours and underwent follow-ups on 1st, 3rd, 6th, and 12th months. Cyst’s volumes and the reduction rate (%) were calculated in each evaluation. Results. No pain or complications were noted. A significant cyst’s volume reduction was documented over time (P<0.001). On the 12th month 17 cysts disappeared and two displayed a 98.7% and 68.9% reduction, respectively. Conclusion. This percutaneous approach constitutes a very promising nonsurgical alternative for patients with symptomatic simple cyst, without complications under proper precautions, leading to eliminating the majority of cysts.